Atividade anti-inflamatória de análogos sintéticos do amburosídeo A de Amburana cearensis A.C Smith em células microgliais: papel das vias de sinalização do NF-κB e MAPKs - Serra Azul, Francisco Vinicius Clemente (2022)
Microglia has immune functions in the central nervous system, including synthesis and release of numerous inflammatory mediators in the neuroimmune-inflammatory response, which has a central role in the development of neurodegenerative diseases of high social impact, such as Parkinson's and Alzheimer's disease, which have pharmacotherapies. that treat symptoms and that sometimes bring a series of adverse effects that make it difficult for patients to adhere to treatment. Thus, considering the current limitations of the pharmacotherapy of these neuroinflammatory diseases, the search for new drugs is essential. Previous studies carried out in our laboratory with animals (rats and mice) and cell lines (neutrophils, BV2, mesencephalic cells) demonstrated the anti-inflammatory, hepatoprotective and neuroprotective effects of the standardized extract and/or amburoside (AMB) of Amburana cearensis (cumaru, Fabaceae). AMB has a low extractive yield, thus, it is strategic to use this molecule as a prototype for laboratory synthesis. The objective of this work was to investigate the anti-inflammatory effect of synthetic analogues of AMB in a model of neuroinflammation in microglial cells of the BV2 lineage. Therefore, the effects of AMB analogues (A23, A30, A33 and A35) on the viability of BV2 cells (MTT test) were investigated. We also investigated the effects of AMB analogues on the production of inflammatory markers (nitric oxide, IL-1β, IL-6 and TNF-α) and the expression of proteins involved in their biosynthesis and cell signaling (iNOS, JNK, ERK, p38, NF-κB) induced by lipopolysaccharide (LPS, 0.5 µg/ml) in BV2 cells. Among the investigated analogues (5-100 µg/ml), a reduction in cell viability of around 60% was observed for analogues A23 and A35 (at concentrations  25 µg/ml), while for A30 this happened at concentrations  50 µg/ml. Non-toxic concentrations were used to proceed with the study. Analogs A23 and A35 (10 µg/ml) reduced NO production by 42% and 77%, respectively, while A30 (25 µg/ml) reduced it by 52%. The A33 analogue did not significantly interfere with the concentration of NO in BV2 cells exposed to LPS. A23 and A35 (most promising analogues) reduced the production of pro-inflammatory cytokines, with the maximum reductions being: IL-1β (A23 10 µg/ml: 54.6%; A35 5 µg/ml: 41.5%), IL-6 (A23 10 µg/ml: 58.7%; A35 10 µg/ml: 36.7%) and TNF-α (A23 10 µg/ml: 89.2%; A35 10 µg/ml: 85.3%). The study proceeded with the most promising A35 (10 µg/ml), which was able to reduce the expression of iNOS (33.1%), JNK (54.8%), ERK (17.2%), p38 (26.7%) and NF-κB (35.6%). The AMB analogs, A23, A30 and A35, have an anti-inflammatory effect on microglial cells, by reducing the production of inflammatory cytokines and/or NO. For A35, this effect seems to be associated with reduced NO biosynthesis, and inhibition of cell signaling pathways, such as NF-κB and MAPKs (JNK, ERK1/2 and p38).